Making the most of mess : reliability and policy in today's management challenges - Roe, Emery (Durham ; London : Duke University Press, 2013)
Emery Roe suggests productive ways to manage ""messes""-complex, large-scale problems that cannot be easily resolved. He develops his argument through an analysis of the 2008 financial crisis and policymakers' responses to it.
Introducing policy messes, management, and their managers -- When reliability is mess management -- The wider framework for managing mess reliably: hubs, skills, and the -- Domain of competence -- Bad mess management -- Good mess management -- Societal challenges -- Professional challenges -- Concluding how we know the mess is managed better.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Policy sciences -- Decision making; Infrastructure (Economics) -- Management; Risk management; Reliability (Engineering); Electronic books